The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1016/s0009-2614(02)01287-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen dissolution history on reconstruction behavior of a stepped metal surface

Abstract: We have observed that the reconstruction dynamics for stepped Ni(9 7 7) are influenced by the oxygen dissolution history of the crystal. Using a complementary approach incorporating both real-and reciprocal-space techniques, it is found that the upper end of the thermal range over which this stepped metal surface transforms from single to double steps increases with selvedge or sub-surface oxygen concentration. These results enhance our understanding of how adsorbate dissolution, and hence oxygen exposure hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In summary, it is not obvious the influence of minute amounts of C in the step doubling phenomenon, in contrast to the clear effect of oxygen. [21][22][23][24] In this context, the present curved crystal approach ensures the same (very low) density of defects and/or impurities in all vicinal planes. Such uniform conditions, under which we have observed step-type asymmetry and critical angle for periodic step-doubling in Ni(111) vicinal surfaces, allow us to discuss the occurrence of the step doubling transition on the grounds of the TWD and the elastic theory.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In summary, it is not obvious the influence of minute amounts of C in the step doubling phenomenon, in contrast to the clear effect of oxygen. [21][22][23][24] In this context, the present curved crystal approach ensures the same (very low) density of defects and/or impurities in all vicinal planes. Such uniform conditions, under which we have observed step-type asymmetry and critical angle for periodic step-doubling in Ni(111) vicinal surfaces, allow us to discuss the occurrence of the step doubling transition on the grounds of the TWD and the elastic theory.…”
Section: Discussionmentioning
confidence: 97%
“…Understanding step-doubling at vicinal surfaces, and particularly the nature of the phase transition, , requires a systematic research of crystals, as a function of temperature and miscut. Ni surfaces, where step-doubling has been claimed in a variety of cases, ,, are good candidates. The first important question that arises is whether step-doubling in Ni surfaces is inherent to the pristine crystal or it is triggered by impurities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An active role of defects in oxygen adsorption was suggested early [204] but it has been assessed systematically only recently, as indicated by the increasing number of publications on defected systems which has appeared in the last few years. For stepped Ni surfaces, e.g., it was shown that: (a) an O-induced missing row reconstruction occurs on Ni(771) [205]; (b) the reconstruction dynamics of O/Ni(977) is influenced by the oxygen dissolution history of the crystal [206] and (c) the heat of adsorption for oxygen at Ni(211) is considerably higher than on any LMI Ni surface, due to the higher reactivity of under-coordinated atoms [108]. For the less investigated Rh and Ru stepped surfaces the attention concentrated mainly on the chemical activity of step atoms [207,208]; for O 2 /Rh(711) [207] it was demonstrated that (111)-like steps are active sites although they are not always the most stable ones for adsorption.…”
Section: Oxygen Adsorption At Noble and Transition Metal Surfaces: Thmentioning
confidence: 99%